Relación entre sueño y rendimiento académico en estudiantes - Müller Torres, Katherine (2022)
Sleep is a physiological state of importance for an optimal development of the human being, it is known that its alteration or deprivation can bring about negative repercussions during the daily activities of an individual. The objective of this research is to identify the relationship between sleep and academic performance in students, through an applicated report review. Taking into consideration the PRISMA guide, the search was carried out in the electronic data bases that ensure the quality standards of the articles: Scopus, Dialnet, Scielo and Google Scholar. The analysis of a total of ten articles was carried out with samples from the different levels of education, elementary school, high school and college. On the hand, we found that there, studies that report a positive relationship between sleep and academic performance and the other hand, there are studies that do not report this relationship. Finally, interventions are proposed from the educational psychologist’s point of view to raise awareness of the importance of sleep and its positive repercussions on development.